2015
DOI: 10.2460/ajvr.76.9.828
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of glomerular filtration rate in dogs by a single-blood sample method involving iodixanol

Abstract: Results indicated that the SBSM involving iodixanol can be applied to estimate GFR in dogs, instead of use of an MBSM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…The GFR measured by the RS‐ and SS‐protocols proved reliable for many clinical situations regardless of the level of renal function. This is in agreement with previous reports that GFR assessed by simplified sampling approaches in companion animals correlates with GFR based on multi‐sample investigations …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The GFR measured by the RS‐ and SS‐protocols proved reliable for many clinical situations regardless of the level of renal function. This is in agreement with previous reports that GFR assessed by simplified sampling approaches in companion animals correlates with GFR based on multi‐sample investigations …”
Section: Discussionsupporting
confidence: 93%
“…The most commonly used method to normalize GFR in dogs is indexation to BW, but some authors prefer to normalize the measurements to BSA, and differences have been reported between the levels of renal function standardized to BW or BSA . In the present study, we observed that the correlation between iohexol plasma clearance and dog body size was lost only when GFR was scaled to BW.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, strategies to reduce the number of sampling have been exploited as first reported by Bröchner-Mortensen (1972) in humans. All of these foresaw the addition of correction formulas to achieve more accurate GFR estimation ( Gleadhill and Michell 1996 ; Bexfield et al, 2008 ; Von Hendy-Willson and Pressler 2011 ; Sasaki et al, 2015 ; Pocar et al, 2019 ). Nevertheless, from veterinary practitioners there is still a demand for reliable and easily applicable GFR estimations methods in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%